Comparing soil nutrient depletion in typical urban, peri-urban and rural farming systems in Ghana - Drechsel, Pay (2002)
In a response to rapid urban growth in Africa, specialized urban and peri-urban vegetable production systems emerge and contribute significantly to urban food security. these production systems are dominated by smallholders and can achieve despite poor soils astonishing high profits. This, however, require intensive fertilization (e.g. 100-200 tiha poultry manure) and year-round irrigation of 600-1600 mm, which adds further nutrients but also contributes to nutrient leaching. In this highly dynamic input-output system fanners are demonstrating that "permanent" cropping is possible on poor tropical soils but for the price of high N and K losses and water eutrophication. The situation is described for the case of lettuce, cabbage and spring onion farming in and around Kumasi, Ghana. Nutrient balances and depletion costs have also been calculated for the more conventional (rural) maize-cassava intercrop for comparison as well as rainfed tomato farming. From fanners point of view, the "costs" of nutrient mining vary with the availability of farm land. In the conventional system, fanner still can to shift when soil fertility is low, thus pay only for the preparation of a new field. In the land constrained urban vegetable system the costs of nutrient mining can best be assessed through their replacement costs via poultry manure or mineral fertilizer. Additional off-site costs of the vegetable system might be balanced through the fertilizer value of the water (for irrigation) and appears in general marginal in comparison with water pollution through the urban run-off.